The Role Of Mothers As Agents Of Enculpturation Of Masculinity In Boys Of Nias Ethnicity In Tegal Sari Mandala II Village, Medan Denai District - Jefrin Milhham Hia; Rosramadhana (Journal Of Global Research Publications, 2025)
This study aims to determine the role of mothers as agents of masculinity enculturation for Nias ethnic boys. This study uses a qualitative method with an ethnographic approach, data collected through participatory observation, in-depth interviews, and documentation of Nias ethnic mothers and boys. The results show that the role of mothers as agents of masculinity enculturation in Nias ethnic boys in Tegal Sari Mandala II Village emphasizes the instilling of masculine values through daily care that is appropriate to the context of urban life. Mothers instill the value of courage by accustoming children to dare to speak, appear, and defend the truth, while building strength through emotional control and assertiveness to be able to face pressure, develop resilience through independence, discipline, and adaptability, and teach leadership through responsibility, decision-making, and the application of traditional leadership values such as si'ulu and si'ila. The main challenges faced by mothers include the stubbornness of children, the limited role without a husband figure for single parents, and the negative influence of social media and diverse urban environments. Mothers make various efforts to overcome these obstacles by implementing a firm but loving parenting style, providing motivation when children experience failure, and involving other male family members such as uncles or church members to provide advice. The implementation of traditional Nias ethnic masculinity values is still attempted through oral narratives, the use of digital technology to demonstrate the Fahombo (Stone Jumping) tradition, and the involvement of boys to attend and witness various Nias ethnic traditions in urban areas to maintain their ethnic identity amidst modernity